Summer regression—the impact of summer on English learners’ reading development - Jaekel, Nils; Jaekel, Julia; Fincher, Elizabeth; Brown, Clara Lee (Frontiers in Education, 2022)
Each summer, students may lose some of the academic abilities they gained over the previous school year. English Learners may be at particular risk of losing English skills over the summer, but they have been neglected in previous research. This study investigates the development of oral reading fluency (ORF) of English Learners compared with native English speakers. Using the AIMSweb Reading Curriculum-Based Measurement in a pre-post design, reading fluency of N=3,280 students (n=363 / 11.1% English Learners versus n=2,917 / 88.9% native speakers) was assessed in a school district in the Southeastern U.S. in May (4th grade) before and September (5th grade) after the summer break. Results showed that, on average, English Learners performed 23.36 points below native speakers after the summer break. However, native English speakers and English Learners lost ORF at similar rates over the summer (β = -.02, p=.281). Contradictory to our hypothesis, students who had been higher performing in the spring had more reading performance losses over the summer (β = -.45, p<.001). Future studies should assess the underlying individual student characteristics and learning mechanisms in more detail in order to develop evidence-based recommendations for tailored programs that can close the achievement gap between English Learners and native English speakers.